Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
If f(x) = 2x - 5 and g(x) = x + 52, then f(g(x)) can be deduced by placing g(x) in the spot of x in the f(x) equation as follows:
f(g(x)) = 2(g(x)) - 5
Since we know g(x) = x + 52, let's plug it in:
f(g(x)) = 2(x + 52) - 5
f(g(x)) = 2x + 104 - 5
f(g(x)) = 2x + 99
f(g(x)) = 2(g(x)) - 5
Since we know g(x) = x + 52, let's plug it in:
f(g(x)) = 2(x + 52) - 5
f(g(x)) = 2x + 104 - 5
f(g(x)) = 2x + 99
f(x) = 2x - 5
g(x) = x + 52
f(g(x)) = 2(x + 52) - 5
f(g(x)) = 2(x) + 2(52) - 5
f(g(x)) = 2x + 104 - 5
f(g(x)) = 2x + 99
or
f(x) = 2x - 5
g(x) = x + 52
f(g(x)) = f(x + 52)
f(g(x)) = (x + 52) + 52
f(g(x)) = x + (52 + 52)
f(g(x)) = x + 104
g(x) = x + 52
f(g(x)) = 2(x + 52) - 5
f(g(x)) = 2(x) + 2(52) - 5
f(g(x)) = 2x + 104 - 5
f(g(x)) = 2x + 99
or
f(x) = 2x - 5
g(x) = x + 52
f(g(x)) = f(x + 52)
f(g(x)) = (x + 52) + 52
f(g(x)) = x + (52 + 52)
f(g(x)) = x + 104
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.